Effect of Animated Instructional Strategy on Gender And Learning Motivation In Chemistry In Ogoja Education Zone, Nigeria - Anari, Mary Ideba; Agim, Francis Betianabeshie; Obi, Joy Joseph (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2025)
This study examined the impact of animated video-based instructional strategies on students’ motivation and gender differences in learning chemistry in Ogoja Local Government Area, Cross River State, Nigeria. Using a quasi-experimental pre-test, post-test design, 200 SSII students were selected from a population of 2,700. The instruments used included the Chemistry Achievement Test (CAT), with a reliability coefficient of 0.85 (KR-20), and a Student Learning Motivation Questionnaire, with a Cronbach alpha of 0.82. Data were analyzed using descriptive statistics and ANCOVA. The findings revealed a statistically significant improvement in students’ motivation towards chemistry for those taught using animated instructional strategies, with F(1, 179) = 6.27, p < 0.001. The mean gain score for the animated group was 20.07, indicating a substantial performance improvement. Furthermore, the effect size, represented by a partial eta squared value of 0.736, suggests a strong practical significance, with the animated strategy accounting for approximately 73.6% of the variance in motivation outcomes. However, the interaction effect between gender and instructional strategy was not statistically significant, with the effect size, represented by a partial eta squared value of .004, suggesting a low practical significance, accounting for approximately 4% of the variance in outcomes, indicating that gender did not influence the effectiveness of the animated method. These results suggest that animation enhances motivation and achievement in chemistry learning regardless of gender. Therefore, it is recommended that chemistry and science educators adopt animated instructional strategies in classroom instruction to improve student engagement and academic performance. Incorporating animation can serve as an effective pedagogical tool to foster deeper understanding and sustained interest in science subjects.